Secondary Malnutrition and Nutritional Intervention in Cholestatic Liver Diseases in Infants - Larrosa-Haro, Alfredo; Caro-Sabido, Erika A. (Frontiers in Nutrition, 2021)
We aimed to conduct an updated review on the pathophysiology, diagnosis, and nutritional intervention of CCLD and secondary malnutrition in infants. Protein-energy malnutrition, impaired linear growth, fat-soluble vitamin deficiencies, and hepatic osteodystrophy can occur in up to 80% of cases. The proposed pathophysiological mechanisms include insufficient energy intake, lipid- and fat-soluble vitamin malabsorption, increased energy expenditure, altered intermediate metabolism, hormonal dysregulation, and systemic inflammation. The current approach to diagnosis is the identification of the deviation of growth parameters, body composition and serum concentration of micronutrients, which determines the type and magnitude of malnutrition. Currently, liver transplantation is the best therapeutic alternative for the reversal of nutritional impairment. Early and effective portoenteroanatomosis can extend survival in patients with biliary atresia. Medical and dietary interventions in some storage and metabolic diseases can improve liver damage and thus the nutritional status. A proportion of patients with biliary atresia have fat-soluble vitamin deficiencies despite receiving these vitamins in a water-soluble form. With aggressive enteral nutrition, it may be possible to increase fat stores and preserve muscle mass and growth. The nutritional issues identified in the pre- and post-transplantation stages include muscle mass loss, bone demineralization, growth retardation and obesity. Due to the implications for the growth and development of infants with CCLD with this complex malnutrition syndrome, innovative projects are required, such as the generation of prediction and risk models, biomarkers of growth and body composition, and effective strategies for nutritional prevention and intervention.